2013
DOI: 10.1155/2013/536369
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Developed Method for the Extraction of Triazines in Surface Waters and Storage Prior to Analysis to Seawaters of Galicia (Northwest Spain)

Abstract: A simple method based on solid-phase extraction combined with liquid chromatography for simultaneous determination of nine triazine herbicides (ametryn, atrazine, cyanazine, prometryn, propazine, simazine, simetryn, terbuthylazine, and terbutryn) in surface water samples was developed and validated. Under optimized conditions, 50 mL of water sample was pumped through the Oasis HLB cartridge, and triazines were eluted with 3 mL acetone. Finally the extract was concentrated to dryness, reconstituted with 1 mL me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Up to date, there are a plethora of commercially available SPE phases, such as octadecyl (C 18 ), oasis hydrophiliclipophilic balanced, styrenedivinylbenzene, and LiChrolut EN [16,39], while SPE is generally available in two different formats, that is, cartridges and disks [6]. However, conventional SPE sorbents might exhibit some drawbacks including high cost and low selectivity and sensitivity [40,41].…”
Section: Development Of Novel Sorbents For the Extraction Of Triazine Herbicidesmentioning
confidence: 99%
“…Up to date, there are a plethora of commercially available SPE phases, such as octadecyl (C 18 ), oasis hydrophiliclipophilic balanced, styrenedivinylbenzene, and LiChrolut EN [16,39], while SPE is generally available in two different formats, that is, cartridges and disks [6]. However, conventional SPE sorbents might exhibit some drawbacks including high cost and low selectivity and sensitivity [40,41].…”
Section: Development Of Novel Sorbents For the Extraction Of Triazine Herbicidesmentioning
confidence: 99%
“…Liquid–liquid extraction (LLE) and solid‐phase extraction (SPE) are widely used to extract triazine species for food analysis . Some researchers used ultrasonic solvent extraction (USE), solid–liquid extraction (SLE), dispersive micro solid‐phase extraction (DMSPE), or matrix solid‐phase dispersion . There are published records of triazine determination by capillary electrophoresis (CE) with the online sample preconcentration technique or by micellar electrokinetic chromatography (MECK) …”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled to mass spectrometry has been widely employed (Sanchez-Ortega et al 2009;Bagheri et al 2010;Djozan et al 2010;Katsumata et al 2010;Matamoros et al 2010;Navarro et al 2010;Portoles et al 2011;Bagheri et al 2012), and the use of liquid chromatography with different detectors such as ultraviolet (Hu et al 2009a, b;Zhou et al 2009;Beale et al 2010;See et al 2010), diode array (Kueseng et al 2009;Wang et al 2010Wang et al , 2011Rodríguez-González et al 2013) or mass spectrometry (Mazzella et al 2009;van Pinxteren et al 2009;Dujakovic et al 2010;García-Galán et al 2010;Postigo et al 2010;Trtic-Petrovic et al 2010;Lissalde et al 2011) was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, solid-phase extraction (SPE) is the preconcentration technique most commonly used for the determination of triazines in water samples (Kueseng et al 2009;Mazzella et al 2009;van Pinxteren et al 2009;Bagheri et al 2010;Dujakovic et al 2010;García-Galán et al 2010;Katsumata et al 2010;Matamoros et al 2010;Navarro et al 2010;Postigo et al 2010;Lissalde et al 2011;Portoles et al 2011;Rodríguez-González et al 2013). However, this technique is being replaced by other fast techniques that minimise the waste of organic solvents according with the principles of green chemistry (Anastas and Eghbali 2010).…”
Section: Introductionmentioning
confidence: 99%